General synthesis of ferrocenylphosphine-bridged digold carboxylato complexes: Crystal and molecular structure of Au2(η1-CF3CO2) 2(μ-dppf) · C6H14 (dppf = Fe(C5H4PPh2)2) - Low, P.M.N. (2014)
Journal of Organometallic Chemistry